2007
DOI: 10.1016/j.cbpc.2006.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Heme crystallization in the midgut of triatomine insects

Abstract: Hemozoin (Hz) is a heme crystal produced by several blood-feeding organisms in order to detoxify free heme released upon hemoglobin (Hb) digestion. Here we show that heme crystallization also occurs in three species of triatomine insects. Ultraviolet-visible and infrared light absorption spectra of insoluble pigments isolated from the midgut of three triatomine species Triatoma infestans, Dipetalogaster maximus and Panstrongylus megistus indicated that all produce Hz. Morphological analysis of T. infestans and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 45 publications
0
31
0
Order By: Relevance
“…Hz crystals have also been observed in close association with PMVM [35], [20]. Previous data from our group have shown that lipids isolated from PMVM are efficient catalysts of Hz formation [30].…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…Hz crystals have also been observed in close association with PMVM [35], [20]. Previous data from our group have shown that lipids isolated from PMVM are efficient catalysts of Hz formation [30].…”
Section: Introductionmentioning
confidence: 62%
“…Some organisms have a particular way to detoxify heme, by forming a dark brown crystal called hemozoin (Hz) [17]. This crystal was first described in the digestive vacuole of malaria parasites ( Plasmodium ) [18] and subsequently in triatomine insects [19], [20], in the helminth Schistosoma species [21] and others [22], [23], representing the major heme detoxification pathway in these organisms. Hz is chemically and structurally identical to a synthetic heme product called β-hematin [24], but the mechanisms involved in biological heme crystallization are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…These organisms are either agents or vectors of serious and highly prevalent diseases, such as schistosomiasis ( Schistosoma mansoni ) and Chagas disease ( Rhodnius prolixus ), that affect a large fraction of the world population. Physical and chemical studies have revealed that the heme-derived pigment found in all the above species is indistinguishable from P. falciparum hemozoin (Chen et al, 2001; Oliveira et al, 2005; Oliveira et al, 2007; Pisciotta et al, 2005). Thus new insights into factors affecting the solubility of heme species or heme detoxification products could contribute to a unified strategy in the fight against all of these medically relevant organisms.…”
Section: Resultsmentioning
confidence: 99%
“…However, crystallization is often associated with a reduction of chemical reactivity, e.g. in blood-feeding insects free heme is crystallized to suppress the generation of free radicals (Oliveira et al, 2007). Carotenoids are also known to help some insects defend against phototoxicity (Aucoin et al,1995).…”
Section: Discussionmentioning
confidence: 99%